Literatura in besedilna posredovanja - Chartier, Roger (Primerjalna književnost, 2010)
Authors do not write books, not even their own books, because books are not the reproduction of an autograph manuscript. The publication of any text, literary or not, implies in Early Modern times multiple mediations and multiple mediators: copysts, editors, compositors, correctors. Following the example of punctuation in English, Spanish, and French texts of the sixteenth and seventeenth centuries, this article would like to show that the process of publication is always a collective one, supposing multiple decisions, and, also, that these decisions, which affect the materiality of the text, are decisive for the construction of the text's meaning.
Keywords: avtorstvo; založništvo; uredniško delo; korekture